Legal Protection for Coastal Communities Regarding the Issuance of Land Certificates for Sea Fence Construction Projects: Perlindungan Hukum Masyarakat Pesisir terhadap Terbitnya Sertifikat Tanah Proyek Pembangunan Pagar Laut - Muhammad Ardian Fatiha Irawan; Ridha Wahyuni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Coastal and marine spaces are constitutionally mandated to be managed by the state for the greatest public welfare, particularly to safeguard the livelihoods of coastal communities that depend on marine resources. Specific Background In Northern Tangerang, the issuance of Building Use Rights (SHGB) for sea fence construction projects by private corporations has restricted fishers’ access to the sea and raised fundamental legal and social concerns. Knowledge Gap Existing studies have not sufficiently integrated constitutional principles, agrarian law, marine governance, and empirical community impacts to assess the legality and implications of granting land rights over marine areas. Aims This study aims to examine the legal validity of SHGB issued over coastal waters and to analyze their implications for social justice, sustainable development, and the protection of coastal communities’ rights. Results Using a juridical-empirical approach, the study finds that SHGB over marine areas are legally invalid due to the absence of Marine Spatial Utilization Permits and the incompatibility of seas as objects of land rights, while empirically causing socio-economic and ecological harm. Novelty The research offers an integrated constitutional–agrarian–marine law analysis grounded in field evidence. Implications The findings support revocation of unlawful SHGB, stronger state oversight in marine governance, and enhanced legal protection for coastal communities to ensure equitable and sustainable coastal development. Highlights: Legal validity: SHGB over marine areas contradict agrarian and marine law principles. Social impact: Sea fence construction restricts fishers’ access and undermines livelihoods. State obligation: Constitutional mandates require equitable and sustainable marine governance. Keywords: Coastal Communities, Marine Governance, Land Rights, Social Justice, Sustainable Development